When “Technology Saves Us”: Exploring and Theorizing Pandemic Pedagogies in Adult ELT Contexts - Kisha Bryan; Quanisha Charles (Journal of English Language Teaching and Linguistics, 2022)
Educators continue to grapple with the ever-changing dynamics of COVID-19 and its effects on teaching and learning. As such, this study contributes to the limited research on the challenges and supports of English language teachers (ELTs) who work with adult learners. Much of the research on teaching during the pandemic has amplified the voices of students, K-12 teachers, and higher education faculty who teach in disciplines where courses are often already offered in online or hybrid formats. In this paper, the researchers highlight the experiences of ELTs in global settings during the onset of the pandemic, when school closure was a necessity and emergency remote teaching was seemingly the only alternative. Utilizing qualitative methodology, data was collected via questionnaires. The researchers provide a thematic analysis of teacher participants’ coping strategies, fears, hopes, challenges, and successes of what is termed ‘pandemic pedagogies for ELT’. The findings suggest that despite the ability for technology to save us, there is a need for more effective ways of responding to and caring for the English language teaching communities amid a global pandemic.